Relationship between surface concentration of l-leucine and bulk powder properties in spray dried formulations - Mangal, S.; Meiser, F.; Tan, G.; Gengenbach, T.; Denman, J.; Rowles, Matthew; Larson, I.; Morton, D. (2015)
The amino acid l-leucine has been demonstrated to act as a lubricant and improve the dispersibility of otherwise cohesive fine particles. It was hypothesized that optimum surface l-leucine concentration is necessary to achieve optimal surface and bulk powder properties. Polyvinylpyrrolidone was spray dried with different concentration of l-leucine and the change in surface composition of the formulations was determined using X-ray photoelectron spectroscopy (XPS) and time of flight-secondary ion mass spectrometry (ToF-SIMS). The formulations were also subjected to powder X-ray diffraction analysis in order to understand the relationship between surface concentration and solid-state properties of l-leucine. In addition, the morphology, surface energy and bulk cohesion of spray dried formulations were also assessed to understand the relation between surface l-leucine concentration and surface and bulk properties. The surface concentration of l-leucine increased with higher feed concentrations and plateaued at about 10% l-leucine. Higher surface l-leucine concentration also resulted in the formation of larger l-leucine crystals and not much change in crystal size was noted above 10% l-leucine. A change in surface morphology of particles from spherical to increasingly corrugated was also observed with increasing surface l-leucine concentration. Specific collapsed/folded over particles were only seen in formulations with 10% or higher l-leucine feed concentration suggesting a change in particle surface formation process. In addition, bulk cohesion also reduced and approached a minimum with 10% l-leucine concentration. Thus, the surface concentration of l-leucine governs particle formation and optimum surface l-leucine concentration results in optimum surface and bulk powder properties.